Cyclodextrin production by bacillus lehensis isolated from cassava starch: Characterisation of a novel enzyme - Blanco, Kate Cristina [UNESP]; De Moraes, Flávio Faria; Bernardi, Natalia Sozza [UNESP]; Vettori, Mary Helen Palmuti Braga [UNESP]; Monti, Rubens [UNESP]; Contiero, Jonas [UNESP] (My University, 2014)
The properties of a previously unknown enzyme, denominated cyclodextrin glycosyltransferase, produced from Bacillus lehensis, were evaluated using affinity chromatography for protein purification. Enzyme characteristics (optimum pH and temperature; pH and temperature stability), the influence of substances on the enzyme activity, enzyme kinetics, and cyclodextrin production were analysed. Cyclodextrin glycosyltransferase was purified up to 320.74-fold by affinity chromatography using β-cyclodextrin as the binder and it exhibited 8.71% activity recovery. This enzyme is a monomer with a molecular weight of 81.27 kDa, as estimated by SDS-PAGE. Optimum temperature and pH for cyclodextrin glycosyltransferase were 55°C and 8.0, respectively. The Michaelis-Menten constant was 8.62 g/l during maximum velocity of 0.858 g/l.h.
Keywords: Affinity chromatography; Cyclodextrin glycosyltransferase; Purification